Generation of Myeloid Cells in Cancer: The Spleen Matters - Wu, Chong; Hua, Qiaomin; Zheng, Limin (Frontiers in Immunology, 2020)
Myeloid cells are key components of the tumor microenvironment and critical regulators of disease progression. These innate immune cells are usually short-lived and require constant replenishment. Emerging evidence indicates that tumors alter the host hematopoietic system and induce the biased differentiation of myeloid cells to tip the balance of the systemic immune activities toward tumor-promoting functions. Altered myelopoiesis is not restricted to the bone marrow and also occurs in extramedullary organs. In this review, we outline the recent advances in the field of cancer-associated myelopoiesis, with a focus on the spleen, the major site of extramedullary hematopoiesis in the cancer setting. We discuss the functional specialization, distinct mechanisms, and clinical relevance of cancer-associated myeloid cell generation from early progenitors in the spleen and its potential as a novel therapeutic target.